Maternal Age Correlates with Stunting in Children: Systematics Review - Astuti, Fardhiasih Dwi; Azka, Arlina; Rokhmayanti, Rokhmayanti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Teenage mother should be ready for the consequences to come. It is important to get prepared both mentally and economically. A teenage mother and her offspring are at risk of malnutrition and stunting. This study aims to analyze the correlation between maternal age and the incidence of stunting based on published articles. Subjects and Method: A systematic review was conducted to find the correlation between maternal age and the incidence of stunting. The research was conducted by seeking into the database by using PubMed, Ebsco, Google Scholar, and SpringerLink. The keywords used were